Houndsley and Catina plink and plunk - Howe, James, 1946-; Gay, Marie-Louise (Somerville, Mass. : Candlewick Press, 2009)
Houndsley likes canoeing and his friend Catina likes bicycling, but each has to help the other learn to enjoy these activities in order to do them together.
Kirkus Review.
3.3
K-3
Keywords: Bicycles -- Juvenile fiction; Canoes and canoeing -- Juvenile fiction; Cats -- Juvenile fiction; Dogs -- Juvenile fiction; Friendship -- Juvenile fiction; Bicycles and bicycling -- Fiction; Canoes and canoeing -- Fiction; Cats -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Canoes and canoeing -- Fiction; Cats -- Fiction; Cycling -- Fiction; Dogs -- Fiction; Friendship -- Fiction